Efektivitas Minyak Jintan Hitam (Nigella Savita Linn) Terhadap Bakteri Staphylococcus epidermidis yang Terdapat Pada Ulkus Diabetik - Indah Armaya Ningrum; Rena Meutia (Journal of Pharmaceutical and Sciences, 2023)
Diabetes mellitus (DM) is a metabolic disease characterized by hyperglycemia (increased blood sugar levels) that occurs due to defects in insulin secretion, insulin action, or both. Black cumin oil (Nigella Savita Linn) is a species in the genus Nigella, which includes about 14 species of plants that contain oily solids, namely unsaturated fatty acids, arachidic acids and eicosadienoic acids, proteins, alkaloids, saponins, essential oil. The aim of this study was to determine the antibiotic activity of black cumin oil (Nigella Savita Linn) on Staphylococcus epidermidis bacteria and to determine the concentration of black cumin oil (Nigella Savita Linn) which can inhibit the growth of Staphylococcus epidermidis bacteria. The results obtained at concentrations with concentrations of 1 mg/mL, 0.75%, 0.5%, and 0.25% have an antibiotic effect on the growth of Staphylococcus epidermidis bacteria found in diabetic ulcers. The differences in the antibiotic effects of black cumin extract (Nigella Savita linn), namely concentrations of 1%, 0.75%, 0.5%, and 0.25%, have significant differences in inhibition so that it can be concluded that black cumin oil (Nigella sativa linn), significantly statistically significant (p and <0.05) inhibited the growth of Staphylococcus cholermidis in diabetic ulcers. The higher the concentration of black seed oil (Nigella sativa) the greater the inhibition zone formation.